Potential of Artificial Intelligence (AI) Implementation for Improving Bridge Maintenance Management: A Case Study on Malaysia – Singapore Second Link Expressway - Zol, Nurul Athirah; Kasim, Narimah; Mohd Noh, Hamidun; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2024)
Maintenance is the activity carried out to conserve, care for, operate, and regulate buildings, facilities, equipment, building services, infrastructure, and its environment to meet current standards and maintain the value of utilities and facilities to be safe to use. Based on previous studies, lack of funds and technology are weak factors in bridge maintenance management. The existing system cannot accommodate extensive data, and the data analysis time is extended. This case study focuses on the Bridge built to connect Malaysia and Singapore, the Malaysia - Singapore Second Link Expressway. The study investigated the potential use of Artificial Intelligence (AI) to improve maintenance management of the Malaysia-Singapore Second Link Expressway. This study aims to examine the current challenges of technology implementation in maintenance management and further discuss the potential performance of AI to improve maintenance management. The study used qualitative methods with a semi-structured interview approach. The respondents involved consisted of four people: the assistant director of operational monitoring, a civil engineer, and an assistant engineer from LLM and PLUS Berhad. The collected data was analyzed using content analysis to provide information from respondents on the potential implementation of AI to improve bridge maintenance management of the Malaysia - Singapore Second Link Expressway. The main finding is that researchers are aware of current technologies being implemented, such as BIM and IoT, along with the significant challenges faced, namely cultural clarity and technology. The second most essential findings leading to the potential implementation of AI are efficiency and effectiveness in the workplace, quality improvement, and product safety and enhancement. In conclusion, this research contributes to an in-depth understanding of technological practices, current challenges, and potential implementation of AI in improving bridge maintenance management for the Malaysia - Singapore Second Link Expressway.